Küpers clinical prediction score in a case series of primary aldosteronism - Paz-Ibarra, José Luis (2023)
Background: Primary aldosteronism is a disorder due to excessive aldosterone production in the presence of low renin levels. It is an underdiagnosed pathology despite its simple screening. Establishing the unilateral or bilateral location represents the greatest diagnostic challenge and is crucial to define the therapeutic approach. Adrenal venous catheterization (AVC) is the best test to establish the location, but it is invasive and expensive. New predictive markers of laterality are being developed. Case series presentation: We present a case series of 8 patients diagnosed with primary aldosteronism due to arterial hypertension with hypokalaemia, elevated aldosterone-renin ratio and compatible computed tomography. 4 patients underwent adrenal venous catheterization. Conclusion: In patients who underwent catheterization as well as in those who did not, the Küpers score adequately predicted lateralization in 75% of cases and it could be a useful tool to discriminate unilateral from bilateral aldosteronism.